The Roles of Non-Coding RNAs in Radiotherapy of Gastrointestinal Carcinoma - Li, Jie; Sun, Juan; Liu, Zhen; Zeng, Ziyang; Ouyang, Siwen; Zhang, Zimu; Ma, Mingwei; Kang, Weiming (Frontiers in Cell and Developmental Biology, 2022)
Radiotherapy (RT), or radiation therapy, has been widely used in clinical practice for the treatment of local advanced gastrointestinal carcinoma. RT causes DNA double-strand breaks leading to cell cytotoxicity and indirectly damages tumor cells by activating downstream genes. Non-coding RNA (including microRNAs, long non-coding RNAs, and circular RNAs) is a type of RNA that does not encode a protein. As the field of non-coding RNAs increasingly expands, new complex roles have gradually emerged for non-coding RNAs in RT. It has been shown that non-coding RNAs can act as radiosensitivity regulators in gastrointestinal carcinoma by affecting DNA damage repair, cell cycle arrest, irradiation-induced apoptosis, cell autophagy, stemness, EMT, and cell pyroptosis. Here, we review the complex roles of non-coding RNAs in RT and gastrointestinal carcinoma. We also discuss the potential clinical significance and predictive value of non-coding RNAs in response to RT for guiding the individualized treatment of patients. This review can serve as a guide for the application of non-coding RNAs as radiosensitivity enhancers, radioresistance inducers, and predictors of response in RT of gastrointestinal carcinoma.